The Hegel variations : on the Phenomenology of spirit - Jameson, Fredric (Verso, 2010)
In this major new study, the philosopher and cultural theorist Fredric Jameson offers a new reading of Hegel's foundational text "The Phenomenology of Spirit". In contrast to those who see The Phenomenology as a closed system ending with Absolute Spirit, Jameson's reading presents an open work in which Hegel has not yet reconstituted himself in terms of a systematic philosophy (Hegelianism) and in which the moments of the dialectic and its levels have not yet been formalized. The ending, on the aftermath of the French Revolution, is interpreted by Jameson as a provisional stalemate between the political and the social, which is here extrapolated to our own time.